2020
DOI: 10.1186/s13034-020-00344-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial distress among in-school adolescents in Mozambique: a cross-sectional study using the Global School-Based Health Survey data

Abstract: Background Poor mental health remains the leading cause of disability, with considerable negative impacts in low- and middle-income countries. In this study, we examined the prevalence and correlates of psychosocial distress among in-school adolescents in Mozambique. Methods This was a cross-sectional study of 1918 in-school adolescents, using data from the 2015 Mozambique Global School-Based Health Survey. Descriptive and inferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
3
9
0
1
Order By: Relevance
“…Female adolescents had a higher susceptibility to emotional distress compared to their male counterparts. This finding is in tandem with other research which opine that female adolescents tend to experience more mental health problems after a stressful life event (Altemus, 2014, Gust et al, 2017, Jin et al, 2019, Amu et al, 2020. A likely explanation for this may be that males tend to easily form peer groups, and discuss their problems with close friends and pals thereby easily getting advice and help with their emotional problems.…”
Section: Female Gendersupporting
confidence: 86%
See 1 more Smart Citation
“…Female adolescents had a higher susceptibility to emotional distress compared to their male counterparts. This finding is in tandem with other research which opine that female adolescents tend to experience more mental health problems after a stressful life event (Altemus, 2014, Gust et al, 2017, Jin et al, 2019, Amu et al, 2020. A likely explanation for this may be that males tend to easily form peer groups, and discuss their problems with close friends and pals thereby easily getting advice and help with their emotional problems.…”
Section: Female Gendersupporting
confidence: 86%
“…Comparable rates of 21.2% (Amu et al, 2020), 15.7% (Siziya et al, 2015), and 16.9% (Seidu et al, 2021) for emotional distress were reported among adolescents in Mozambique, Zambia and Tanzania respectively. However a lower rate of 12% was found in Nigeria, (Omigbodun et al, 2008) this may have been due to methodological differences between this study and the present one.…”
Section: Prevalence Of Emotional Distressmentioning
confidence: 97%
“…While these are clear strengths of our study, there are also several limitations. We defined psychological distress among adolescents based on self-reported data on five mental health variables, according to a previously published study (28) . We acknowledge that the conceptualisation of a complex phenomenon like psychological distress can still be incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions, questions, and coding methods for the variables used in this study are shown in supplementary table S1. Following previous studies (28) investigating psychological distress, we defined "psychological distress" based on five mental health variables available in the GSHS dataanxiety, loneliness, suicidal ideation, suicide planning, and suicide attempt. The original responses to the survey questions for these variables were converted into dichotomous responses where 0 = no and 1 = yes.…”
Section: Variable Definitionsmentioning
confidence: 99%
“…Another study by Amu H, et al . [ 14 ] showed that the prevalence of mental distress was 21.2%. More in females and older adolescents.…”
Section: Discussionmentioning
confidence: 99%